2013
DOI: 10.1111/nicc.12030
|View full text |Cite
|
Sign up to set email alerts
|

International overview of high‐level simulation education initiatives in relation to critical care

Abstract: The use of simulation in health care education has become very topical across all professions and specialties in order to improve patient safety and quality of care. In the last decade, the adoption of more realistic simulation-based teaching methodologies, which serves as a bridge between the acquisition and application of clinical skills, knowledge, and attributes, has been accompanied by the development of a multitude of international and national simulation societies. These serve as important exchange fora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 35 publications
1
25
0
1
Order By: Relevance
“…A growing body of literature provides evidence that high fidelity simulation improves knowledge acquisition and critical thinking of undergraduate nursing students, [20] as well as self-efficacy and learner satisfaction, [21][22][23] and that the knowledge and skills gained from simulation practice transfers directly to the point of care. [22,24,25] Consistent with the literature, students in accelerated baccalaureate programs engaged in high fidelity simulation report learner satisfaction and increased self-efficacy and competence for clinical practice. [26,27] A key challenge in the integration and use of high fidelity simulation in nursing curricula is the measurement and evaluation of clinical competencies.…”
Section: Introductionsupporting
confidence: 65%
“…A growing body of literature provides evidence that high fidelity simulation improves knowledge acquisition and critical thinking of undergraduate nursing students, [20] as well as self-efficacy and learner satisfaction, [21][22][23] and that the knowledge and skills gained from simulation practice transfers directly to the point of care. [22,24,25] Consistent with the literature, students in accelerated baccalaureate programs engaged in high fidelity simulation report learner satisfaction and increased self-efficacy and competence for clinical practice. [26,27] A key challenge in the integration and use of high fidelity simulation in nursing curricula is the measurement and evaluation of clinical competencies.…”
Section: Introductionsupporting
confidence: 65%
“…While some of the principles of using simulation in the education of pre-registration students is applicable to the postregistration setting, it is inappropriate to assume the same processes will be effective in improving skills and changing practice for the registered nurse. The literature has identified that the effectiveness of simulation-based learning for post-registration nurses is still largely unknown (Alinier and Platt 2013), and furthermore there is limited empirical evidence to support the overall effect simulation has on clinical practice, with regard to the transfer of knowledge and skills clinical practice (Murray et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Within critical care, simulation has become a mainstay pedagogical approach advocated by a range of critical care societies including the Intensive Care Society (ICS), the Royal College of Anaesthetists (RCoA) and most recently by the British Association of Critical Care Nurses. In their international review of simulation use, Alinier and Platt () conclude that simulation as an educational strategy may provide an effective way to increase patient safety. Studies reported by Alinier and Platt () showed that investment in simulation training can produce significant health care cost savings.…”
Section: So What?mentioning
confidence: 99%
“…In their international review of simulation use, Alinier and Platt () conclude that simulation as an educational strategy may provide an effective way to increase patient safety. Studies reported by Alinier and Platt () showed that investment in simulation training can produce significant health care cost savings.…”
Section: So What?mentioning
confidence: 99%